2006
DOI: 10.1111/j.1467-7687.2006.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of area discrimination and its implications for number representation in infancy

Abstract: This paper investigates the ability of infants to attend to continuous stimulus variables and how this capacity relates to the representation of number. We examined the change in area needed by 6-month-old infants to detect a difference in the size of a single element (Elmo face). Infants successfully discriminated a 1:4, 1:3 and 1:2 change in the area of the Elmo face but failed to discriminate a 2:3 change. In addition, the novelty preference was linearly related to the ratio difference between the novel and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
158
4
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(177 citation statements)
references
References 27 publications
14
158
4
1
Order By: Relevance
“…As described earlier, numerical discriminations are modulated by the ratio between the values, as per Weber's law. In human infants, the ratio effects for judgments of size, time, and number are refined at a similar rate of development (11,51,52). Infants' discriminations of size, time, and number improve by approximately 30% between 6 and 9 mo of age.…”
Section: For Review)mentioning
confidence: 99%
“…As described earlier, numerical discriminations are modulated by the ratio between the values, as per Weber's law. In human infants, the ratio effects for judgments of size, time, and number are refined at a similar rate of development (11,51,52). Infants' discriminations of size, time, and number improve by approximately 30% between 6 and 9 mo of age.…”
Section: For Review)mentioning
confidence: 99%
“…In particular, it was shown that infants (5.5-7.5 months) could distinguish between dowels of different height when another object, serving as a standard, was present; they could not make such distinctions when no standard was available (Duffy, Huttenlocher, Levine, & Duffy, 2005;Huttenlocher, Duffy, & Levine, 2002;see also, Feigenson, Carey, & Spelke, 2002). There is evidence that only when the sizes being compared involve fairly large differences are infants (and older children) capable of making spatial discriminations in the absence of a standard (e.g., Brannon, Lutz, & Cordes, 2006;Huttenlocher et al, 2002).…”
Section: Object Sizementioning
confidence: 99%
“…Looking time studies revealed that 5-month-old infants are sensitive to changes in metric distances (Newcombe, Huttenlocher, & Learmonth, 1999;Newcombe, Sluzenski & Huttenlocher, 2005), and toddlers encode distance metrically in a hide-and-seek game (Huttenlocher, Newcombe, & Sandberg, 1994). Furthermore, magnitude coding is used early in life, as evidenced by infants' discrimination of space, time, number, and speed (Brannon, Lutz, & Cordes, 2006;Brannon, Suanda, & Libertus, 2007;Möhring, Libertus, & Bertin, 2012;Xu & Spelke, 2000), and recent studies yielded evidence for cross-dimensional transfer, suggesting that magnitude information regarding various dimensions is coded in one representational system (de Hevia & Spelke, 2010;Lourenco & Longo, 2010). It is likely that metric understanding is based on this fundamental comparative system, termed the general magnitude system (Walsh, 2003).…”
mentioning
confidence: 99%